Introduction of tesla automotive system into directional grids of small towns - Kostandov, T. (ТДАТУ, 2018)
Unfortunately, air pollution is a main problem of all cars, that is why most of us live in smog-choked cities and this is what our immunity cannot withstand and protect our health from. The greatest solution of this problem is transition from usage of petrol vehicles to driving Tesla cars.
Keywords: air pollution; smog-choked; health; Tesla automotive system